2004
DOI: 10.1002/hed.10350
|View full text |Cite
|
Sign up to set email alerts
|

Tailored endoscopic surgery for the treatment of sinonasal inverted papilloma

Abstract: Tailored endoscopic surgery is a safe and effective treatment that obviates the need for more extensive surgery for the management of inverted papilloma. Proper preoperative evaluations, intraoperative determination of extent and attachment of the tumor, close endoscopic follow-up, and expert application of endoscopic techniques are the keys to the successful use of tailored endoscopic surgery.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
51
1
4

Year Published

2007
2007
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 46 publications
(58 citation statements)
references
References 22 publications
(26 reference statements)
2
51
1
4
Order By: Relevance
“…ER for IP now appears to be at least as effective in tumor control as more traditional open approaches but avoids morbidity associated with the traditional open approaches 1–19 . Systemic reviews by Krouse 4 and Busquets and Hwang 7 have demonstrated this in pooled data comparisons.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…ER for IP now appears to be at least as effective in tumor control as more traditional open approaches but avoids morbidity associated with the traditional open approaches 1–19 . Systemic reviews by Krouse 4 and Busquets and Hwang 7 have demonstrated this in pooled data comparisons.…”
Section: Discussionmentioning
confidence: 99%
“…Despite a lack of stage‐based comparisons, further evidence has accumulated to suggest that ER and OMM result in comparable overall recurrence rates (RR). Concurrently, some reports since 2000 have begun to report outcomes based on the Krouse staging system 4–18 . However, other reports have omitted this information, stressing the lack of global acceptance for currently available staging 19–23 .…”
Section: Introductionmentioning
confidence: 99%
“…Tailored endoscopic surgery is a safe and effective treatment that obviates the need for more extensive surgery for the management of inverted papilloma [360]. Endoscopic medial maxillectomy (EMM) is a safe, effective method for the treatment as well as for diagnosis and followup in all patients [283, 426, 471, 472].…”
Section: Treatmentmentioning
confidence: 99%
“…[7][8][9][26][27][28] However, more surgeons are accepting a more tailored or sequential segmental endoscopic surgical procedure based on the extent of disease. 29 Residual disease and small recurrences frequently may be removed with inoffice procedures, with particularly good results in nasoethmoid disease. Frontal disease or extensive maxillary disease frequently results in the need for additional resection under general anesthesia.…”
Section: Inverted Papillomasmentioning
confidence: 99%